Microstructural Characterization of a Magnesium Alloy Processed by Equal Channel Angular Pressing - Dumitru, Florina Diana; Moncea, Mihaela Andreea; Higuera-Cobos, Oscar Fabián (Universidad Pedagógica y Tecnológica de Colombia, 2014)
Samples of as-extruded ZK60 magnesium alloy were subjected to 6 passes of equal-channel angular pressing (ECAP) following route A. The processing temperature was decreased with the number of passes. The structural evolution of the deformed samples was analyzed using Electron Backscattered Diffraction (EBSD) and X-Ray Diffraction. The grain boundary misorientation distribution showed a reduction in the grain size accompanied bya large proportion of high angle grain boundaries and the presence of recrystallization processes. XRD results showed that with the increment of the applied strain the peaks presented a slight variation of the angles.